1998
DOI: 10.1016/s0735-1097(98)00128-4
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic Assessment of Regionalized Defects in Myocardial Sympathetic Innervation and Blood Flow Regulation in Diabetic Patients With Autonomic Neuropathy

Abstract: DAN is associated with altered myocardial blood flow, with regions of persistent sympathetic innervation exhibiting the greatest deficits of vasodilator reserve. Future studies are required to evaluate the etiology of these abnormalities and to evaluate the contribution of the persistent islands of innervation to sudden cardiac death complicating diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
3
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 47 publications
8
67
3
1
Order By: Relevance
“…However, most of the previous studies have included patients with both Type 1 and Type 2 diabetes or other potentially confounding factors such as diabetic complications, smoking, hypertension, obesity and lipid abnormalities, which are known to further reduce coronary vasoreactivity. Consistent with the results of the present study, the findings of one previous PET study demonstrated that patients with Type 1 diabetes and autonomic neuropathy have decreased adenosinestimulated coronary vasoreactivity, while the non-neuropathic Type 1 diabetic patients have unaltered myocardial blood flow and coronary flow reserve [28]. Thus, the question of whether coronary reactivity is impaired in non-complicated Type 1 diabetes is still being debated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, most of the previous studies have included patients with both Type 1 and Type 2 diabetes or other potentially confounding factors such as diabetic complications, smoking, hypertension, obesity and lipid abnormalities, which are known to further reduce coronary vasoreactivity. Consistent with the results of the present study, the findings of one previous PET study demonstrated that patients with Type 1 diabetes and autonomic neuropathy have decreased adenosinestimulated coronary vasoreactivity, while the non-neuropathic Type 1 diabetic patients have unaltered myocardial blood flow and coronary flow reserve [28]. Thus, the question of whether coronary reactivity is impaired in non-complicated Type 1 diabetes is still being debated.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, coronary vasoreactivity has been found to be either normal [28] or more frequently decreased [8,29,30,31,32] in diabetic patients. However, most of the previous studies have included patients with both Type 1 and Type 2 diabetes or other potentially confounding factors such as diabetic complications, smoking, hypertension, obesity and lipid abnormalities, which are known to further reduce coronary vasoreactivity.…”
Section: Discussionmentioning
confidence: 90%
“…The increased flow at baseline and the diminished increase in relative blood flow and venous oxygen saturation over the course of haemodialysis in the diabetic group suggest the presence of neuropathy. A similar observation has been made in the myocardium, in which neurogenic reflexes play an important role in controlling tissue microcirculation [16,17]. Nevertheless, we cannot rule out the possibility that the differences we observed could have resulted from different degrees of arterial calcification in the two groups.…”
Section: Discussionsupporting
confidence: 74%
“…* p = 0.012, ** p < 0.001 [109] Type II diabetic patients [109, 113±115]. Recent studies suggest that cardiac sympathetic dysfunction affecting cardiac sympathetic efferent sympathetic signals is directly related to coronary blood flow in diabetes [109,113,116]. Sympathetically mediated myocardial blood flow, as induced by cold pressor test, was increased by 31 % in diabetic patients without scintigraphically assessed cardiac sympathetic dysinnervation compared with only 14 % in diabetic patients with cardiac sympathetic dysinnervation [113].…”
Section: Coronary Blood Flow Reservementioning
confidence: 99%